EFFECT OF AQUEOUS ALOE VERA EXTRACT AS ROOT CANAL IRRIGANT ON ROOT FRACTURE RESISTANCE: A COMPARATIVE IN VITRO STUDY - Murtatha M. Ubaid; Raghad A. Al-Hashimi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to evaluate the effect of aqueous Aloe vera on susceptibility to root fracture resistance (RFR) in human teeth subjected to endodontic preparation, and compare it with chemical irrigants (sodium hypochlorite (NaOCl), ethylenediaminetetraacetic acid (EDTA), and SmearOFF). A total of 40 human maxillary first molars that were extracted and had a straight palatal root. These roots were distributed randomly based on the irrigation regimes (n=8): G1: Distilled water; G2: 3% NaOCl; G3: 3% NaOCl + 17% EDTA; G4: Smearoff; and G5: 90% Aloe vera, and then endodontically prepared using the ProTaper Next rotary system. The samples were placed within acrylic molds using periodontal simulation and exposed to compressive forces at a rate of 0.5 mm/min until fracture was noted. The specimens undergo axial forces on a universal testing machine during mechanical compression testing. The force necessary for fracture was measured and recorded in Newton (N). The results showed that the mean fracture resistance of Aloe vera group was the highest while NaOCl group was the lowest. It can be concluded that, the fracture resistance was significantly different in various irrigation protocols.